Evaluation of the Cell Death Induction of Gold Nanoparticles Conjugated Antibodies Produced Against a Small Epitope of DR5 Protein in MCF7 Cells - Amirijavid, Shaghayegh; Entezari, Maliheh; Dehghani, Hossein (Archives of Advances in Biosciences, 2019)
Introduction: Nowadays, versatile and useful features of nanoparticles, especially gold nanoparticles in medicine and healthcare have brought them immense popularity. The ability to transfer towards the special cells, distinguish the different cells and their electrical resonance feature make them as a proper candidate for treatment of cancer. Antibodies which are generated against death receptor, DR5, are powerful tools in the programmed death of cancer cells during induction process. Its association with nanoparticles could efficiently deliver such biological apoptosis inducing drug to the cancer cells Materials and Methods: In this study, at the first step, gold nanoparticles were produced by chemical methods in the presence of aspartic acid (amino acid). Then, nano-sized ones were selected and subsequently conjugated by mouse antibodies which were produced against a small 21 amino acid peptide from extracellular domain of death receptor, DR5. Results: The conjugated antibodies by gold nanoparticles could efficiently kill the MCF7 breast cancer cells through inducing cell death. The combination of antibodies which were generated against a small fragment of the death receptor, Conclusion:DR, with gold nanoparticles not only minimized the required amount for the purpose of inducing cell death.but also maximizing their efficiency and quality.